« Condamnés à l’immobilité » - David Scheer (Sociologies, 2015)
This article aims to highlight the mobility imaginaries as a form of criminal punishment. A brief architectural analysis of prisons built in Belgium demonstrates the extreme spatial immobility in which inmates are condemned. It can therefore be balanced with discourses advocating openness, mobility and the involvement of prisoners in the prison process. The hyper-segmentation of spaces, the formalisation of circulations and the dependency on staff are decrypted. The penitentiary "project" is also analysed in this article. Social spaces constrained by the need to avoid any form of reunification (religious, in particular), the weak training offer or the internal mutation strategies illustrate in another way the condemnation to immobility. By analyzing the prison confinement from this angle, and evoking the words of prisoners on immobility – being locked without the opportunity for physical and social mobility or integrating the stigma of being locked by refusing mobility –, it is possible to consider the prison sentence as the withdrawal of one of the fundamental values of our society: mobility; and finally to question the eternal disciplinary quest behind the prison.